2006
DOI: 10.1001/archfaci.8.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Antibiotic Usage by Facial Plastic Surgeons

Abstract: Objectives:To determine current practice for use of perioperative antibiotics among facial plastic surgeons, to determine the extent of use of literature support for preferences of facial plastic surgeons, and to compare patterns of use with nationally supported evidencebased guidelines.Methods: A link to a Web site containing a questionnaire on perioperative antibiotic use was e-mailed to more than 1000 facial plastic surgeons in the United States. Responses were archived in a dedicated database and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Despite the current lack of evidence, the fear of SSIs is still considerably larger than the fear of possible adverse effects or antimicrobial resistance resulting from prolonged antibiotic administration. [3][4][5][6][7] As a result, antibiotic prophylaxis regimens are often prolonged when they might not be necessary. [3][4][5][6][7] However, in light of the antimicrobial resistance issue, the increased risk of serious postoperative adverse effects, and additional pharmaceutical costs, it is becoming extremely difficult to ignore the need for solid evidence on the ideal duration of postoperative antibiotic prophylaxis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the current lack of evidence, the fear of SSIs is still considerably larger than the fear of possible adverse effects or antimicrobial resistance resulting from prolonged antibiotic administration. [3][4][5][6][7] As a result, antibiotic prophylaxis regimens are often prolonged when they might not be necessary. [3][4][5][6][7] However, in light of the antimicrobial resistance issue, the increased risk of serious postoperative adverse effects, and additional pharmaceutical costs, it is becoming extremely difficult to ignore the need for solid evidence on the ideal duration of postoperative antibiotic prophylaxis.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] As a result, antibiotic prophylaxis regimens are often prolonged when they might not be necessary. [3][4][5][6][7] However, in light of the antimicrobial resistance issue, the increased risk of serious postoperative adverse effects, and additional pharmaceutical costs, it is becoming extremely difficult to ignore the need for solid evidence on the ideal duration of postoperative antibiotic prophylaxis. The aim of this study is to systematically review the literature and perform a metaanalysis focused on the association of SSIs with use of shortcourse antibiotic prophylaxis (≤24 hours) vs extendedcourse antibiotic prophylaxis (≥72 hours) after ENT and OMF surgery.…”
mentioning
confidence: 99%
“…Several surveys have shown that a majority of plastic surgeons use antibiotics for facial plastic surgical procedures, although few studies support this. 2 , 8 , 32 Albeit postoperative infections are rare after plastic surgery, plastic surgeons most commonly overprescribe antibiotics as cosmetic infections can seriously affect the aesthetic outcome, which may not be as big of a concern in noncosmetic operations. Given that overusing antibiotics in rhinoplasty and septorhinoplasty cases is more the norm, a behavior change must occur in surgeons to be a part of the solution in decreasing AMR.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO and rhinoplasty guidelines recommend antibiotics not be used for > 24 hours postoperatively, as is often done, due to a low risk of infection. 12 , 15 , 31 Grunebaum and Reiter 32 found that 49% of surgeons use antibiotics postoperatively for > 24 hours. Another survey noted that of 440 surgeons using antibiotics, 31% used antibiotics for > 4 days after rhinoplasty.…”
Section: Role Of Postoperative Antibioticsmentioning
confidence: 99%
“…2,3 Because of this concern, despite the generally low incidence of SSIs in facial plastic surgery procedures, many surveyed clinicians prescribe postoperative antibiotics for SSI prophylaxis. 2,4,5 However, the risk of infection must be balanced with the risks of antibiotic use such as antibiotic resistance and superinfection. 6 Therefore, it is essential to understand the current literature regarding evidence-based infection prevention, as well as areas where more research is needed.…”
mentioning
confidence: 99%